Preparation Metal Complexes of New Schiff Base Derived From 2-Aminoanthraquinone and 3-Acetyl Furan - Yousif, Thana Y.; Aziz, Kawakib A.; Al Quaba, Rana A. S. (Iraqi Journal of Science, 2025)
In the present study, new metal complexes were synthesized using the reactive chemicals 2-amino anthraquinone and 3-acetyl furan to produce novel Schiff base ligands in molar ratios of 1:1 and 1:2 (metal to ligand) with the resultant complexes having the formulas [MLCl] and [ML2Cl2]. Several physicochemical techniques (Elemental analysis, molar conductivity, IR, UV-Vis spectroscopy and magnetic measurements) were used to characterize the complexes. Measurements of conductivity showed that none of the compounds were electrolytes. According to magnetic moment and electronic spectra, certain complexes have a tetrahedral geometry, while others have an octahedral geometry. In both circumstances, the ligand functions as a bidentate chelating ligand. Furthermore, biological assays reveal that several of the newly synthesized complexes demonstrate antibacterial properties, effectively inhibiting the proliferation of specific bacterial strains.